Factors Influencing Credit Risk and Insurance Risk in General Insurance of Indonesia : Technical Reserve Ratio and Reinsurance Ratio (Financial Management Literature Review) - Willib Wong (Dinasti Publisher, 2022)
This article is a Literature Review to see whether there is an effect of the Technical Reserve ratio and the Reinsurance ratio on credit risk and insurance risk in General Insurance in Indonesia. The purpose of this scientific article is to build a causality research hypothesis between variables so that it can be used for further research. The topic of discussion is the area of ????financial management science. The method of writing this Literature Review article is Library Research with sources of books, journals and research articles contained in online media such as Google Scholar, Mendeley, Research gate and other academic media. From this literature review, it can be concluded that 1) the Technical Reserve ratio has an effect on credit risk; 2) Reinsurance ratio has an effect on credit risk; 3) Technical Reserve ratio has an effect on insurance risk; 4) Reinsurance ratio has an effect on insurance risk; and 5) insurance risk affects credit risk. Apart from these 2 exogenous variables that affect the 2 endogenous variables of credit risk and insurance risk, there are many other factors including the loss ratio, current ratio and total assets variables.